Effect of sleep duration and physical activity on certain important body composition parameters among medical students - Modi, Sarita; Siddiqui, Nazeem; Bose, Sukhwant (Asian Journal of Medical Sciences, 2016)
Background: In this highly advanced era and competitive world everyday life offers less time for sleep and physical activity and the result is serious consequences on physical fitness and health of the society and particularly the young generation. Aims and Objectives:The present study was undertaken to find out the influence of sleep deprivation and physical activity on body composition parameters of college students. Materials and Methods: Total 98 students of MBBS 1st professional at Sri Aurobindo Medical College and Post Graduate Institute, Indore of both sexes were recruited for the study. Students were divided as Adequate sleep duration at night (ASDN ≥7 hours) and Inadequate sleep duration at night (ISDN <7 hours) groups Anthropometric measurements were done and information of sleep parameters and physical activity recorded. Body composition analysis was done by Bio-impedance analysis (BIA). Results: Sleep duration was significantly associated with Body fat %(BF%) and Body mass index (BMI) in boys but not in girls. There was significant difference in obesity parameters like BF% and BMI between ASDN and ISDN in both sexes. Significant difference was also observed on comparing Physical activity with BF% and BMI of entire group. Conclusion: sleep length is inversely associated with obesity in boys but not in girls. It also affects physical activity which further aggravates obesity. Asian Journal of Medical Sciences Vol.7(5) 2016 56-60